ANALYSIS OF LEARNING ORGANIZATION IN NURSES AT BOGOR ISLAMIC HOSPITAL - Darmastuti, Meirina (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
ABSTRACT The success of an organization is largely determined by its ability to develop into a learning organization. Learning organization will affect employee performance which then impactshe organization's competitive advantage, including at the Bogor Islamic Hospital. This research aims to determine the implementation of learning organizations in nurses at Bogor Islamic Hospital and its obstacles. This research is descriptive research that uses the Fish Bone analysis method. The data were collected using questionnaires and interviews with 37 nurses, also from Bogor Islamic Hospital’s report documents within years. Almost all of the respondent (97%) agree with the concept of learning organization. But there are still found a lot of learning disabilities in nurses, which implementsearning organizations not yet optimal. Through Fish bone analysis, it was found that the obstacles to implementinthe learning organization were clarity of vision, learning opportunities, human resource management policies, leadership support, and information communication technology support. Implementing learning organization especially for nurses at the Bogor Islamic Hospital needs immediate attention from hospital management so that the Bogor Islamic Hospital canevelop and compete with other hospitals.